ANALISIS BIAYA MUTU DALAM MENINGKATKAN DAYA SAING PENDIDIKAN - Ahmad Fauzi (JUMPA : Jurnal Manajemen Pendidikan, 2020)
Quality education is an expensive investment. Public awareness to bear the cost of education in essence will give a power to the community to be responsible for the delivery of education. Quality costs are costs that if there were no such costs, then an educational institution that we live will continue to run but will not be in accordance with what we expect or are expected by the community. The 1945 Constitution and Law No.20 of 2003 concerning the National Education System are legally binding, the Indonesian State mandates the government to set an education budget of 20 percent of the State budget as stipulated in article 31 paragraph 4.The purpose of this study is to identify the factors that affect the cost of education, types of education costs and models of education financing that are effective and efficient. This study was conducted by conducting a descriptive analysis of documents relating to education costs. The results of the study indicate that factors affecting the cost of education include: a) increases in prices b) changes in teacher salaries c) changes in population and increases in the percentage of children in public schools d) increases in education standards e) increases in guidance for higher education. Types of education costs include: a) direct costs b) indirect costs c) personal costs d) community costs, an effective and efficient educational funding model that is a human capital model where aspects of financing can affect the level of productivity that can affect the level of income of a person or group so can ultimately contribute to the speed of economic growth and development.Keywords : Quality Costs, Educational Institutions, competitiveness